ANALYSIS THE BANK’S HEALTH LEVEL AND RETURN OF STOCK OF BANKING IN INDONESIAN STOCK EXCHANGE - Safri, Hayanuddin; Prayoga, Yudi; Hendry, Raja Saul Marto (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2020)
Bank is the finance institution, beside that Bank also as one of corporate sector in Indonesia, which has important role in promoting the economy system. Therefore management in banking companies which listed on Bursa Efek Indonesia  (Indonesia Stock Exchange) must keep  financial performance through their health level in order  optimize the return of stock. This study aims to determine the effect of risk profile variables measured by the Non Performing Loan (NPL) and Loan to Deposit Ratio (LDR), Variable Earnings as measured by Return On Assets (ROA) and Cost Operational and Operating Income (BOPO) as well as the measured capital variables with Capital Adequacy Ratio (CAR) on profit growth. This research is a causal associative research. Population in the study includes 8 banking companies listed on the Indonesia Stock Exchange 2013- 2017. Sampling technique used is purposive sampling and obtained sample as much as the company. Data used in this research is a secondary data that is financial statements that meet the criteria.Data derived from financial statements obtained from Bank Indonesia (BI) which may be accessed through www.bi.go.id and www.idx.co.id. Data analysis uses multiple linear regressions. The result of the research shows that there are variables that have positive effect to return of stock is CAR variable, ROE, and BOPO variable while variable ROA andLDR have no effect on profit growth, and NPL has negative effect to Return of stock.. Ability variable independent in explaining the variation of the dependent variable equal to 57,6%, whereas the remaining 41.5% is explained by other independent variables outside the model research.